PENGARUH TANGIBLE, RELIABILITY, RESPONSIVENES, ASSURANCE DAN EMPHATY TERHADAP KEPUASAN KONSUMEN (Survei Konsumen Rumah di CV Satria Graha Gedongan, Colomadu, Karanganyar) - Rahayu - Triastity; Sri Lestari Triyaningsih (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2013)
ABSTRACT Target of this research is (1) to Significant Influence Tangible, Reliability, Responsiveness, Assurance and Emphaty to Customer Satisfaction (2) to analysis factor which having an effect on dominant to Costumer Satisfaction. Result of research show (1) Examination of hypothesis by partial (test t). Shal be as followe: Tangible Variable Reliability, Responsiveness, Assurance and Emphaty have an effect significant to consumer satisfaction, (2) Examination of hypothesis accuracy of model (F test) show F value corelated equal to 55,848 whit level of significant 0,000. Probably value 0,000 < 0,05 mater give meaning that examination of used by model that is Tangible factor, Reliability Responsiveness, Assurance and Emphaty proven by at time have an effect signifi-cant to costumer satisfaction, (3) Tangible factor have strongest contribution in influency costumer satisfaction. This matter because of level of regression coefficient value equal to 0,287 is which the biggest to be compared with fourt of other variable. Keywords: Tangible, Reliability, Responsiveness, Assurance, Emphaty Consumer statisfaction.